Trichinella infections in animals and humans of Iran and Turkey - Borhani, Mehdi; Fathi, Saeid; Harandi, Majid Fasihi; Simsek, Sami; Ahmed, Haroon; Wu, Xiaoxia; Liu, Mingyuan (Frontiers in Medicine, 2023)
Trichinellosis is considered as a cosmopolitan zoonosis caused by different species of the small nematodes of the genus Trichinella. The present study aimed to provide a broad review for exploring Trichinella sp. infection in humans and animals of Iran and Turkey. Additionally, we aimed to explore bases for trichinellosis prevention and control. Two reports of human trichinellosis following the consumption of meat of wild boar are available in the northern Iran. A large outbreak of trichinellosis and some other sporadic cases are reported mainly as a result of eating wild boar or pork meat from Turkey, where T. britovi is present. Field studies show that Trichinella sp. infections occur in wild carnivores of Iran, particularly the golden jackal (Canis aureus) as the most frequently infected species. T. britovi has been reported to be present elsewhere in Iran in wild mammals, where wild boar is the main source of Trichinella sp. infection. In Turkey, Trichinella spp. has been reported from animals including both domesticated and wild pigs and gray wolf (Canis lupus). However, current data on the distribution of Trichinella taxa are fragmentary in the Anatolian region.